Role of oxidative stress in rem sleep deprivation-induced endothelial dysfunction in rat model - Nor, Nur Syafiqah Mohmed (2020)
Sleep deprivation is associated with endothelial dysfunction, an early sign of cardiovascular disease. The pathogenesis underlying endothelial dysfunction in sleep deprivation remains poorly understood to date. The objective of this study was to identify the possible factors involved in the mechanism of endothelial dysfunction in sleep deprivation, in particular REM sleep phase. Only experiments for the first objective were carried out in this study as a result of the Movement Control Order (MCO) of the Federal Government of Malaysia due to the pandemic of coronavirus disease (COVID-19). Eight (8) male Sprague-Dawley rats were equally divided into four groups; free-moving control rats (FMC), 72-h REM sleep-deprived rats (REMsd), tank control rats (TC) and sleep recovery for 72 hours after 72 hours of REM sleep deprivation rats (SR). Rats were deprived of REM sleep using the inverted flowerpot technique. There was no significant differences in the levels of food consumption, body weight gain and systolic blood pressure between the groups. The levels of protein expression of endothelial nitric oxide synthase (eNOS) and phosphorylated eNOS (peNOS), and the levels of oxidative stress markers in the aorta; total antioxidant capacity (TAC), catalase (CAT), and superoxide dismutase (SOD) were not measured due to time constraints. Based on the assumption that REM sleep deprivation induced endothelial dysfunction, it is expected that there will be a significant decrease in the levels of p-eNOS in the REMsd group compared to other groups. Oxidative stress has been postulated as a possible factor in the mechanism of endothelial dysfunction, thus a significant decrease in the levels of antioxidants is expected to occur in aortic tissue. In conclusion, it is postulated that REM sleep deprivation is associated with endothelial dysfunction that may be induced by oxidative stress